Expanding drainage capacity of open drains by utilising the same corridor as that of the drain reserve without compromising the intended function of the drainage - Loh, Win Yew (2019)
As climate change continues to disrupt our daily lives, actions must be taken to ensure that our lives will not be disrupted by such changes. One of the biggest challenges that Singapore faces is the disruption of rainfall patterns. As a country with limited land, there is only that much space we can dedicate to drainage and storage of rainwater. As the climate changes, Singapore experiences more short but intense rainfall. The high volume of rainwater that falls over a short duration of time overwhelms the existing drainage system and causes issues like flooding. It is therefore paramount to reduce the vulnerability of our land to these disruptions as much as possible. This report delivers a conceptual design of a water detention tank for urban rainfall events. The proposed design will be integrated into the neighborhood with a constructed observation tower to blend into the surrounding, improving aesthetics. This study analyzed the existing solutions implemented to tackle the flooding issue and provide further methods to improve on the current drainage infrastructure. The project will be assessed based on the following criteria pertaining to the construction of a surface water detention tank in Singapore. The criteria include understanding the design considerations involved for the construction of the proposed structure and discussing possible limitation that may arise with this proposal.